Pivotal Role of the C-terminal DW-motif in Mediating Inhibition of Pyruvate Dehydrogenase Kinase 2 by Dichloroacetate - Li, Jun (American Society for Biochemistry and Molecular Biology, 2009)
The mitochondrial pyruvate dehydrogenase complex (PDC) is down-regulated by phosphorylation catalyzed by pyruvate dehydrogenase kinase (PDK) isoforms 1–4. Overexpression of PDK isoforms and therefore reduced PDC activity prevails in cancer and diabetes. In the present study, we investigated the role of the invariant C-terminal DW-motif in inhibition of human PDK2 by dichloroacetate (DCA). Substitutions were made in the DW-motif (Asp-382 and Trp-383) and its interacting residues (Tyr-145 and Arg-149) in the other subunit of PDK2 homodimer. Single and double mutants show 20–60% residual activities that are not stimulated by the PDC core. The R149A and Y145F/R149A mutants show drastic increases in apparent IC(50) values for DCA, whereas binding affinities for DCA are comparable with wild-type PDK2. Both R149A and Y145F variants exhibit increased similar affinities for ADP and ATP, mimicking the effects of DCA. The R149A and the DW-motif mutations (D382A/W383A) forestall binding of the lipoyl domain of PDC to these mutants, analogous to wild-type PDK2 in the presence of DCA and ADP. In contrast, the binding of a dihydrolipoamide mimetic AZD7545 is largely unaffected in these PDK2 variants. Our results illuminate the pivotal role of the DW-motif in mediating communications between the DCA-, the nucleotide-, and the lipoyl domain-binding sites. This signaling network locks PDK2 in the inactive closed conformation, which is in equilibrium with the active open conformation without DCA and ADP. These results implicate the DW-motif anchoring site as a drug target for the inhibition of aberrant PDK activity in cancer and diabetes.